THE DEEP LEARNING APPROACH IN SOCIOLOGY EDUCATION AT THE HIGH SCHOOL LEVEL - Fritz Hotman Syahmahita Damanik; Gibran Muhammad (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2025)
The study explores the integration of deep learning approaches into high school Sociology education, addressing the need for transformative teaching methodologies in an era of increasing complexity in social dynamics. Sociology, with its focus on understanding societal structures and relationships, provides an ideal platform for employing deep learning strategies such as project-based learning, case studies, and reflective discussions. These methods encourage critical thinking, problem-solving, and the ability to connect theoretical knowledge with real-world issues, fostering both academic and personal growth. Utilizing a qualitative methodology and a literature review approach, the research synthesizes insights from recent studies within the last five years, emphasizing their relevance and credibility. Findings reveal that deep learning enhances students' analytical skills, empathy, and cultural awareness, bridging the gap between classroom theories and real-world applications. The study highlights the need for professional development for educators, supportive policies, and equitable learning environments to address implementation challenges. Future research should examine the long-term impact of deep learning on students' academic and career trajectories and explore technological advancements in facilitating this approach. By advocating for deep learning in Sociology, the study underscores its potential to nurture socially conscious individuals equipped to navigate and address contemporary societal complexities.